The factor analysis of groundwater quality data of the Tista floodplain and the Dharla floodplain, Kurigram, Bangladesh: Siderite dissolution is a source of iron in groundwater - H.M. Selim Reza, A.; Saha, Sudip (International Journal of Advanced Geosciences, 2020)
The present research work deals with the hydrochemical nature of the groundwater samples of the Dharla and the Tista River floodplains of Kurigram district, Bangladesh. The mechanism of groundwater chemistry was studied from the Gibbs plot and it can be summarized that precipitation and rock-water interaction are the major factors that influence the groundwater chemistry. The first four factors comprise 83.243% of the total variability of the groundwater samples of the Dharla floodplain aquifer whereas in case of the groundwater of the aquifers of the Tista floodplain first five factors constitute the 81.298% of the total variability of the original data. The study shows the dominance of HCO3-1 in the anionic part of the groundwater. More than 73.68% of the groundwater samples of the aquifers of the Tista floodplain exceed the maximum permissible limit of WHO for arsenic. The groundwater samples from the Tista floodplain especially from some parts of Rajarhat have high concentrations of iron. The first factor of the Dharla floodplain is dominated by iron and HCO3-1 ions which suggests the derivation of iron in the groundwater of the study area from the chemical weathering of siderite (FeCO3).